"It's not their fault": Clinical facilitators' experiences supporting English as second language students. Issue 1 (February 2023) - Lim, Eric; Kalembo, Fatch; Bosco, Anna; Ngune, Irene; Adebayo, Bola; Brown, Janie
Abstract: Background: International nursing students in Australia are faced with additional stress and challenges during clinical placements due to language and cultural differences. These factors can significantly impact their learning experience and personal wellbeing. Aim: This study aimed to explore the clinical facilitators' perspectives of the experiences of international nursing students and the potential strategies for improving their learning experiences during clinical placements. Methods: An exploratory qualitative study was designed. Semistructured interviews with 14 participants were conducted and analysed using thematic analysis. Findings: The findings were categorised into two categories. (1) Clinical facilitators' perspectives on the international nursing students' experiences during the clinical placements, and (2) Clinical facilitators' perspectives on strategies for improving the learning experience of international nursing students. Category 1 consisted of three themes: (i) Reduce self-confidence when communicating in English, (ii) Lowered perceived self-efficacy, and (iii) Looking for a sense of belonging. Category 2 consisted of five themes: (i) Nurture a supportive environment, (ii) Use validating and understanding communications, (iii) Promote acceptance of the cultural and language diversities, (iv) Use strength-based approaches, and (v) Create opportunities for transcultural socialisation. Discussion: Clinical facilitators are well-positioned to support international nursing students to achieve positive learning experiences during clinical placements. More support from the university and hospital may be needed to enable clinical facilitators to effectively implement the identified potential strategies. Conclusion: The study findings provided the background for future research to upskill clinical facilitators and support them to facilitate positive experiences for international nursing students during clinical placements.